3‐Mercaptopyruvate sulfurtransferase represses tumour progression and predicts prognosis in hepatocellular carcinoma. (12th March 2022) - Li, Meng; Song, Xin; Jin, Qi; Chen, Yishu; Zhang, Jie; Gao, Jianguo; Cen, Li; Lin, Yiming; Xu, Chengfu; He, Xinjue; Li, Youming; Yu, Chaohui
Abstract: Background and: Aims: The prognosis of hepatocellular carcinoma (HCC) remains dismal, and its molecular pathogenesis has not been completely defined. The enzyme 3‐mercaptopyruvate sulfurtransferase (MPST) regulates endogenous hydrogen sulfide (H2 S) biosynthesis. However, the role of MPST in HCC has never been intensively investigated. Methods: MPST protein expression was analysed in HCC tumour tissues and matched adjacent tissues. The effect of MPST on HCC progression was studied in vitro and in vivo. Results: The mRNA and protein expression of MPST was significantly downregulated in HCC samples compared with their paired nontumour counterparts. A low MPST expression was associated with larger tumour size and a worse overall survival. Overexpression of MPST in HCC cells inhibited cell proliferation and induced apoptosis. MPST overexpression also significantly suppressed the growth of tumour xenografts in nude mice, whereas silencing MPST by intratumour delivery of siRNA substantially promoted tumour growth. Moreover, diethylnitrosamine‐induced mouse HCC was aggravated by MPST gene knockout. Mechanistically, MPST suppressed the cell cycle associated with H2 S production and inhibition of the AKT/FOXO3a/Rb signalling pathway in HCC development. In addition, MPST expression negatively correlated with that of pRb in HCC specimens and the combination of these two parameters is a more powerful predictor of poor prognosis. Conclusions: MPST may function as a tumour suppressor gene that plays an essential role in HCC proliferation and liver tumorigenesis. It is a candidate predictor of clinical outcome in patients with HCC and may be used as a biomarker and intervention target for new therapeutic strategies.